2005
DOI: 10.1107/s0108270104030975
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding patterns in 2-amino-4,6-dimethylpyrimidinium hydrogen sulfate

Abstract: In the title compound, C6H10N3+.HSO4-, the asymmetric unit consists of a hydrogen sulfate anion and a 2-amino-4,6-dimethylpyrimidinium cation. The hydrogen sulfate anions self-assemble through O-H...O hydrogen bonds, forming supramolecular chains along the b axis, while the organic cations form base pairs via N-H...N hydrogen bonds. The aminopyrimidinium cations join to the sulfate anions via a pair of hydrogen bonds donated from the pyrimidinium protonation site and from the exo amine group cis to the protona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…The aminopyrimidinium cations are embedded between these zigzag chains. This type of zigzag supramolecular chain of hydrogen sulfate ions has also been reported in the crystal structures of 2-amino-4,6dimethylpyrimidinium hydrogen sulfate (Hemamalini et al, 2005), 8-hydroxy-5,7-dimethylquinolin-1-ium hydrogen sulfate (Thanigaimani et al, 2013) and anilinium hydrogen sulfate (Boutobba et al, 2010). The three-dimensional supramolecular architecture is shown in Fig.…”
Section: Resultssupporting
confidence: 72%
“…The aminopyrimidinium cations are embedded between these zigzag chains. This type of zigzag supramolecular chain of hydrogen sulfate ions has also been reported in the crystal structures of 2-amino-4,6dimethylpyrimidinium hydrogen sulfate (Hemamalini et al, 2005), 8-hydroxy-5,7-dimethylquinolin-1-ium hydrogen sulfate (Thanigaimani et al, 2013) and anilinium hydrogen sulfate (Boutobba et al, 2010). The three-dimensional supramolecular architecture is shown in Fig.…”
Section: Resultssupporting
confidence: 72%
“…We report herein on the synthesis and crystal structure of the title molecular salt. The geometric parameters are comparable with those of similar structures (Moghimi et al, 2004;Hemamalini et al, 2005) The title molecular salt, Fig. 1, contains a 2-amino-1-methyl-5H-imidazolium-4-one cation (protonated at the N atom, N1, in the imidazole unit) and a 4-methylbenzenesulfonate anion (deprotonated at the hydroxyl O atom, O1).…”
Section: Structure Descriptionsupporting
confidence: 64%
“…The crystal structures of aminopyrimidine derivatives (Schwalbe & Williams, 1982), aminopyrimidine carboxylates (Hu et al, 2002) and co-crystal structures (Chinnakali et al, 1999) have been reported. The crystal structures of 2-amino-4,6-dimethylpyrimidinium bromide 2-amino-4,6-dimethyl-pyrimidine monohydrate (Panneerselvam et al, 2004), 2amino-4,6-dimethylpyrimidinium hydrogen sulfate (Hemamalini et al, 2005) and bis(2,4-diamino-6-oxopyrimidinium) sulfate monohydrate (Muthiah et al, 2004) have been recently reported from our laboratory. Most of the supramolecular crystals originate from strong N-HÁ Á ÁO and O-HÁ Á ÁN hydrogen bonds, and weak C-HÁ Á ÁO bonds are known to play a significant role in determining the molecular packing of organic solids (Taylor & Kennard, 1982).…”
Section: Commentmentioning
confidence: 99%